A Quantitative Assessment of the Burden and Distribution of Lisch Nodules in Adults with Neurofibromatosis Type 1 - Boley, Sean (2009)
PURPOSE: The presence of two or more Lisch nodules (melanocytic hamartomas of the iris) is one of seven diagnostic criteria for neurofibromatosis type 1 (NF1), a common monogenic disorder of dysregulated neurocutaneous growth. We investigated the hypothesis that Lisch nodules arise secondary to ultraviolet (UV) radiation exposure from sunlight. METHODS: We mapped and quantified Lisch nodule burden in the irides of 77 adults with NF1. We also inventoried lifetime sunlight (UV radiation) exposure, determined NF1 neurocutaneous severity, and selectively genotyped two NF1 mutations predictive of severity. RESULTS: There was high inter-individual variability in Lisch nodule burden. Lisch nodules were primarily located in the inferior hemifield (half) of the iris, regardless of its color (P = 3.0 × 10(−20)). Light irides harbored significantly more Lisch nodules than dark irides (P = 4.8 × 10(−5)). There was no statistically significant correlation of Lisch nodule burden to lifetime sunlight exposure “dose” or NF1 neurocutaneous severity. CONCLUSIONS: The difference in Lisch nodule burden between the superior and inferior iris hemifields is likely due to the sunlight-shielding effects on the superior half by peri-ocular structures. The difference in Lisch nodule burden between light and dark irides is likely due to the photo-protective effects of pigmentation. The genes underlying the control of iris color may thus be viewed as modifiers of severity of Lisch nodule burden in NF1. Given the role of UV radiation and, presumably, DNA damage in Lisch nodule pathogenesis, “benign tumor of the iris,” not “hamartoma,” may be a better descriptor.